2009
DOI: 10.1021/jf803164u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Feeding of Low Monomer Content Grape Seed Extract on Vitellogenin Production and Cholesterol Levels in Goldfish, Carassius auratus

Abstract: Grape seed extract (GSE) is a source of naturally occurring compounds known as proanthocyanidins and flavan-3-ols, which are recognized to exert a protective effect on human health, so GSE is widely used mainly as a nutritional supplement. However, polyphenols may have, in some cases, estrogenic effects or may interfere with the endocrine system. For that reason, it was considered of interest to investigate the beneficial or detrimental effects induced by low monomer content grape seed extract (LMC-GSE) in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In a pilot experiment, the dose used in this study was tried and confirmed to be suitable and effective in test fish; on the contrary, lower doses than 20 mg aloe/g diet did not result in significant modulation of plasma lipid profile (data non shown). The concentration of E2 was also chosen based on its ability to maximally induce VTG (Palermo et al 2009).…”
Section: Test Dietsmentioning
confidence: 99%
“…In a pilot experiment, the dose used in this study was tried and confirmed to be suitable and effective in test fish; on the contrary, lower doses than 20 mg aloe/g diet did not result in significant modulation of plasma lipid profile (data non shown). The concentration of E2 was also chosen based on its ability to maximally induce VTG (Palermo et al 2009).…”
Section: Test Dietsmentioning
confidence: 99%